MEDICAL REFORM: UKRAINE’S REALITIES AND INTERNATIONAL EXPERIENCE - Ямненко, Тетяна Михайлівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the goal is to analyze the national and international legislation on ensuring the rights of patients and to explore the main trends in the development of the medical sector in Ukraine and foreign countries. Methods: international acts on the protection of patients’ rights were used, which were studied with the use of content analysis, bibliosemantic and analytical experience. Results of the study and their discussion: the need for an analysis of the best evidence-based practices in management, planning, financing, organization of medical care is relevant for many countries in the world. Particular attention is focused on the study and analysis of the organization and methods of financing such institutions.